Texting in a crisis—using SMS for information and emotional support during COVID-19: A mixed methods research study - Wang, Mengdi; Wang, Changzheng; Peng, Xiaobing (Frontiers in Sociology, 2022)
In the era of new media, short message service (SMS) is no longer seen as advantageous and it is no longer used very much by the Chinese public. However, as a traditional media, local governments managing public health crises used SMS as a way of meeting the public's need for emotional support during the COVID-19 pandemic. Our study examined 108 SMS texts pushed to phones in Chongqing between January and December 2020, and carried out in-depth interviews with ten interviewees. This mixed research method of descriptive and grounded theory analysis was designed to investigate how SMS was used to communicate prevention guidelines and give emotional support during COVID-19. The results show that Chongqing Municipal Health and Health Commission gained the public's attention with SMS messages consisting of neutral, objective advice, and guidance to reduce people's anxiety and panic. However, with the stabilization of COVID-19, SMS has once again been discarded by users, including the public health sector. The study found that the emotional support offered by SMS was limited to the elderly, a subset of the population considered to be weak users of the internet. SMS has been replaced by other technologies, but along with other media, such as official media and social media, it has shaped the media communication environment and served as an emotional support channel for the public. Undoubtedly,the use of SMS during COVID-19 presents a research opportunity for exploring its capacity for prevention, control and emotional support.